(untitled) (Arsi Journal of Science and Innovation, 2024)
ABSTRACT The study focused on Livestock’s and Livestock Products Marketing effect on Pastoral Community Economic Status with mediation of market intermediaries in Ethiopia. The sample size is 384 samples and the selected sampling strategies are multistage, purposive, and simple random sampling. Study used quantitative data analysis research approach. This study employs KMO, EFA, CFA, and SEM using AMOS software to investigate the underlying structure of a set of variables. The Kaiser-Meyer-Olkin (KMO) measure confirmed the adequacy of the sample for factor analysis, while Exploratory Factor Analysis (EFA) identified key dimensions within the data. Confirmatory Factor Analysis (CFA) validated the factor structure, ensuring model fit and reliability. Subsequently, Structural Equation Modeling (SEM) assessed the relationships among the latent variables. The results of AMOS demonstrated that the mediation of marketing intermediaries is essential for the sale of commodities and livestock in order to improve the economic status of Ethiopia's pastoralist community. These links also imply that livestock trading by itself (without the assistance of marketing intermediaries) would not enhance the economic status of the pastoralist group. Since marketing intermediates are the ones who are fully mediating the relationship, policy makers should concentrate on them. It implies that intermediaries play a critical role in the marketing process and are essential to the survival of the pastoral economy.